The Association Between Morningness-Eveningness Preference, Depression, Anxiety and Insomnia Among Chinese Textile Workers With or Without Shift Work - Jiang, Jiaqi; Wang, Dongfang; Scherffius, Andrew; Chen, Dingxuan; Ma, Zijuan; Chen, Zihao; Zhang, Yifan; Yu, Qian; Fan, Fang (Frontiers in Psychiatry, 2022)
Abstract Objective: Circadian preference and mental health disorders are closely related to insomnia. The present study aimed to evaluate insomnia symptoms in textile factory workers with different work schedules, and to investigate the association between insomnia, morningness-eveningness preference, anxiety and depression. Methods: A total of 3883 textile workers were assessed using the 3-items of Pittsburg Sleep Quality Index, Composite Scale of Morningness, Beck Anxiety Inventory, Center for Epidemiologic Studies Depression Scale and socio-demographic questionnaires. Results: The prevalence rate of insomnia in textile workers was 16.7% (N = 646), with 49.8% (N = 322) were shift workers. Among shift workers (N = 1833), 9.5% had difficulty initiating sleep, and almost 9.0% suffered from early morning awakening, a rate significantly higher than among daytime workers. Logistics regressions revealed that work schedule was insignificantly associated with insomnia. Depression (OR = 1.034, 95%CI = 1.022 - 1.046) and anxiety (OR = 1.031, 95%CI = 1.018 - 1.043) positively predicted insomnia, whereas morningness preference (OR = 0.977, 95%CI = 0.960 - 0.995) decreased the likelihood of insomnia. Furthermore, mediation analysis showed that both anxiety and depression independently mediated the association between circadian preferences and insomnia in textile workers with or without shift work. Conclusions: The present study highlighted the insomnia, depression and anxiety of textile factory workers in a Chinese textile factory. To improve insomnia symptoms, interventions to promote morningness circadian preference and reduce depressive and anxious symptoms among workers are encouraged.